2019
DOI: 10.1002/nla.2271
|View full text |Cite
|
Sign up to set email alerts
|

Convergence analysis for parallel‐in‐time solution of hyperbolic systems

Abstract: Summary Parallel‐in‐time algorithms have been successfully employed for reducing time‐to‐solution of a variety of partial differential equations, especially for diffusive (parabolic‐type) equations. A major failing of parallel‐in‐time approaches to date, however, is that most methods show instabilities or poor convergence for hyperbolic problems. This paper focuses on the analysis of the convergence behavior of multigrid methods for the parallel‐in‐time solution of hyperbolic problems. Three analysis tools are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…Instead, one should choose Ψ to be some approximation of Φ m -or equivalently, it should approximate taking m steps with Φ on the fine grid-under the constraint that its action is significantly cheaper to compute so that speed-up can be achieved. Typically Ψ is chosen through the process of rediscretizing Φ on the coarse grid, whereby it is employed with the enlarged coarse-grid time step, mΔt, 4,12,23 but other techniques have also been considered. 8,17 For completeness, we now describe all of the settings used in our numerical tests.…”
Section: Mgrit Parareal and Numerical Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, one should choose Ψ to be some approximation of Φ m -or equivalently, it should approximate taking m steps with Φ on the fine grid-under the constraint that its action is significantly cheaper to compute so that speed-up can be achieved. Typically Ψ is chosen through the process of rediscretizing Φ on the coarse grid, whereby it is employed with the enlarged coarse-grid time step, mΔt, 4,12,23 but other techniques have also been considered. 8,17 For completeness, we now describe all of the settings used in our numerical tests.…”
Section: Mgrit Parareal and Numerical Set-upmentioning
confidence: 99%
“…In all of these works, speed-ups over sequential time-stepping for hyperbolic PDEs are typically quite small (on the order of two to six), with slow convergence of the iteration ultimately inhibiting faster runtimes due to increased parallelism. For comparison, a speed-up on the order of 20 times was achieved for a diffusion-dominated parabolic problem in Falgout et al 9 A number of theoretical convergence analyses have been developed for Parareal and MGRIT, 5,12,13,19,[23][24][25][26][27] which have helped to explain numerical convergence results, and will likely play an important role in the design of new solvers. Furthermore, some theoretical studies have identified potential roadblocks for fast parallel-in-time convergence of hyperbolic PDEs.…”
mentioning
confidence: 99%
“…For Runge-Kutta schemes, the number of such operations can be reduced by only computing the eigenvalues of the spatial operator L and evaluating the stability function, as opposed to computing the eigenvalues for the family of Φ for all considered Runge-Kutta schemes. While this might not be possible in general, the derivation of Fourier symbols [3] can provide another viable path to reduce the time complexity of computing such bounds. Furthermore, with prior knowledge of L (e.g., L is symmetric positive definite or skew symmetric), the need for solving an eigenvalue problem can be avoided.…”
Section: Number Of Levels Convergence Factormentioning
confidence: 99%
“…Here, N x refers to the number of degrees of freedom at one point in time, and N t refers to the number of time points. 2 For the theoretical analysis, we consider equidistant time points, δ tn = t n − t n−1 = δ t , and a time-independent one-step integrator, Φ n = Φ, for all n. 3 In matrix form, (2.1) can be written as,…”
mentioning
confidence: 99%
See 1 more Smart Citation